2018
DOI: 10.19126/suje.349339
|View full text |Cite
|
Sign up to set email alerts
|

Ergen annelerine Uygulanan Ebeveyn Stresini Yönetme Programı’nın Etkililiği

Abstract: Öz. Bu araştırma, TEOG sınavına hazırlanan ergenlerin annelerine uygulanan Ebeveyn Stresini Yönetme Programı'nın (ESYP) annelerin anne-babalık stres ve ebeveyn mantıkdışı inanç düzeylerine ve ergenlerin anne baba beklentilerine ilişkin stres ve mantıkdışı inanç düzeylerine etkisini inceleyen yarı deneysel bir çalışmadır. Araştırmada Anne-Baba Stres Ölçeği, Anne-Babaların Akılcı Olmayan İnanç Ölçeği, Anne Baba Beklenti Ölçeği ve Ergenlerde Mantıkdışı İnanç Ölçeği kullanılmıştır. Araştırma 16 anne ve 16 ergen üz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Although there is no clear opinion on the effect of parental involvement depending on gender or age, it is reported that positive feedback and motivating expressions contribute to the treatment process in adolescents (Lock et al 2010, Couturier et al 2013, Ünver 2017. When the findings were evaluated in general, 82.36% of all studies (n = 14; Hudson and Rapee 2001, Khanna and Kendall 2009, Lock et al 2010, Couturier et al 2013, Öngider and Baykara 2015, Elkins et al 2016, Börekçi 2017, Ünver 2017, Arıcı-Özcan and Arslan 2018, Amel et al 2018, Stjerneklar et al 2018, Leyfer et al 2018, Waite et al 2019, Taylor et al 2021) parent involvement was effective, 17.64%' ü (n = 3; Tekinsav- Sütçü et al 2006, Kendall et al 2008, Hughes et al 2009 show that parental involvement reduces the efficiency of the process. In addition, 94.8% of studies (n = 15) tested the effectiveness of parent involvement with different sources.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is no clear opinion on the effect of parental involvement depending on gender or age, it is reported that positive feedback and motivating expressions contribute to the treatment process in adolescents (Lock et al 2010, Couturier et al 2013, Ünver 2017. When the findings were evaluated in general, 82.36% of all studies (n = 14; Hudson and Rapee 2001, Khanna and Kendall 2009, Lock et al 2010, Couturier et al 2013, Öngider and Baykara 2015, Elkins et al 2016, Börekçi 2017, Ünver 2017, Arıcı-Özcan and Arslan 2018, Amel et al 2018, Stjerneklar et al 2018, Leyfer et al 2018, Waite et al 2019, Taylor et al 2021) parent involvement was effective, 17.64%' ü (n = 3; Tekinsav- Sütçü et al 2006, Kendall et al 2008, Hughes et al 2009 show that parental involvement reduces the efficiency of the process. In addition, 94.8% of studies (n = 15) tested the effectiveness of parent involvement with different sources.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, parents can realize that existing strategies that include excessive control and protection may be useless and that some conflicts and dysfunctions in the family can be prevented (Ginsburg and Schlossberg 2002). On the other hand, parents could be found in all of the studies (Öngider and Baykara 2015, Arıcı-Özcan and Arslan 2018, Amel et al 2018, Stjerneklar et al 2018, Leyfer et al 2018, Taylor et al 2021 or some of them (Elkins 2016, Börekçi 2017, Ünver 2017, Waite et al 2019), whether they were in a group, short or long-term therapy, directly participated in the session or received information training (Tekinsav-Sütçü et al 2006, Hughes 2009, Öngider and Baykara 2015, Ünver 2017, Stjerneklar 2018 are also thought to be effective on satisfaction levels. Amel et al (2018) found higher levels of treatment satisfaction among parents who completed parent sessions than among those who did not.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation